The Reconstruction of Career in Changing Workplaces - Duarte, Márcia de Freitas; Silva, André Luis (Organizações & Sociedade, 2014)
This article aims to understand how the employees who faced, in 2006, a process of acquisition of a financial institution where they were employed by a national one, managed to rebuild their careers in this experienced situation. This is a qualitative and descriptive research which also presents a cross sectional cut and longitudinal perspective. Data were produced through interviews with remaining employees and interpreted using the content analysis technique. The results showed that the impacts emerged in the workplace acted as triggers to new career cycles. Using coping strategies against the process of acquisition, the employees reconfigured the meaning of the situation, finding ways to rethink their goals and objectives.